Pola Topografi Pewarnaan Tetrazolium sebagai Tolok Ukur Viabilitas dan Vigor Benih Kedelai (Glycine max L.Merr.) untuk Pendugaan Pertumbuhan Tanaman di Lapangan - , Dina; Eny Widajati; Baran Wirawan; Satriyas Ilyas (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2007)
Topographical tetrazolium (TZ) pattern to determine viability, vigor and field stand on soybean seeds cv. Burangrang was studied. Laboratory test for standard germination, vigor index, speed of germination, accelerated aging, seedling growth rate and field performances were performed on five lots (A,B,C,D,E) of soybean seeds. The viability and vigor categories of each pattern were determined by Root Mean Square (RMS), regression, and correlation analysis. Ten topographical patterns were recognized. The laboratory test results and field performances were compared with topographical pattern. Combination of patterns 1,2,3,4 (embryonic axis and cotyledon completely and/or gradually stained) selected as viable category as it gave the least RMS value, the highest determination (R2) and correlation (r) coefficient with standard germination (RMS=6,46; R2=0,37; r=0,61). Combination of patterns 1,2,3 (embryonic axis and cotyledon completely stained) selected as vigor category as it gave the least RMS value, the highest R2and r with relative speed of germination (RMS=7,96; R2=0,44; r=0,66), vigor index (RMS=6,66; R2=0,36; r=0,6), field emergence (R2=0,79; r=0,89) and field stand (R2=0,65; r=0,80). The combination of patterns 1,2,3 is recommended for estimating field emergence and field stand. Key words : Tetrazolium, topographical pattern, viability, vigor, accelerated aging, field stand, soybean seed.